Modeling of elemental sulfur deposition in sour-gas petroleum pipelines - Zhu, Z.; Tajallipour, N.; Teevens, P.; Lepková, K.; Gubner, Rolf (2011)
Sulfur deposition has been a prominent internal corrosion accelerant issue in sour gas pipeline production operations. In this paper, a theoretical model is proposed to predict the behaviour of elemental sulfur (S8) deposition in a sour-gas petroleum pipeline. During theoretical modeling, pressure and temperature profiles are firstly calculated. Then S8 solubility alteration along the pipeline was acquired. When the initial sulfur-vapor concentration in the gas stream reached the solubility value, the saturation distance was obtained. Further, a decrease in pressure or temperature causes a thermodynamic instability. Once a threshold of free energy change is overcome, elemental sulfur is precipitated. The nucleation rate was determined from classic nucleation theory. Particle coagulation and agglomeration were approximated using the Smoluchowski's analytic model. The precipitated amount in each pipeline subregion was achieved in terms of solubility change. As a result, transient particle size was assessed. Sulfur particle trajectories were tracked by solving the motion equation in which an empirical formula was assigned for turbulent single-phase gas flow. As particles touched the metal surface, the Tabakoff's model was applied for the interaction between particles and the pipeline metal surface. Consequently, the maximum travelling distance of the particles could be quantified. Furthermore, the effects of initial production rate, S8 vapour concentration, pressure and temperature on S8 deposition behaviours were characterized.